From great depression to great recession : the elusive quest for international policy cooperation - Ghosh, Atish R.; Qureshi, Mahvash Saeed (Washington, D.C International Monetary Fund (IMF), 2017)
​Abstract The global financial crisis and the ensuing Great Recession raised concerns about adjustment fatigue, deflation, currency wars, and secular stagnation that presented a sense of déjà vu: similar concerns had arisen at the time of the Great Depression and at the end of World War II. As with earlier crises, these concerns prompted calls for greater international policy cooperation-both to achieve a sustainable recovery from the crisis and to prevent future crises. This volume compiles papers from a 2015 symposium of eminent scholars convened by the IMF to discuss how history can inform current debates about the functioning and challenges of the international monetary system. An introductory chapter sets the stage for the other chapters in the volume by giving a broad overview of the performance of the international monetary system over the past century, highlighting the key events and challenges that shaped it. Subsequent sections look at historical antecedents of today's challenges, describe how the modern international monetary system has been-and continues to be-shaped through international financial diplomacy, provide a present-day perspective, and examine the analytics of international policy coordination.
​Foreword -- Preface -- Abbreviations -- Contributors -- 1. From great depression to great recession: an overview / Atish R. Ghosh, Mahvash S. Qureshi -- Part I. Prespectives from the past: secular stagnation and asymmetric burden of adjustment -- 2. Learning lessons from previous crises: the capital account and the current account / Harold James -- 3. Debastes about economic adjustment in Europe before the Euro / Emmanuel Mourlon-Druol -- 4. Coordination failures during and after Bretton Woods / Catherine R. Schenk -- 5. Capital flows and intenational order: trilemmas and trde-offs from macroeconomics to political economy and international relations / Michael D. Bordo and Harold James -- Part II. Internationa monetary negoriations and the international monetary system -- 6. Forgotten foundations of Bretton Woods / Eric Helleiner -- 7. Hurling BRICS at the international monetary system / Benn Steil -- 8. The IMF is--or was?--the keystone of the international financial system / James M. Boughton -- Part III. Currency wars and secular stagnation--the new normal? -- 9. Reform of the international monetary system: a modest proposal / Richard N. Cooper -- 10. Global bond market spillovers from monetary policy and reserve management / Rober N. McCauley -- 11. International liquidity and overnance / Edwin M. Truman -- Part IV. Prospects for the future: toward a more cooperative system -- 12. Three myths about international policy coordination / Atish R. Ghosh -- 13. Moving toward a more cooperative international monetarysystem / Maurice Obstfeld -- 14. Reforming the global reserve system / José Antonio Ocampo -- 15. Macroeconomic policy: what and how to coordinate internationally / Alexander K. Swoboda -- 16. Toward a more cooperative international monetary system: some remarks / Paul A. Volcker -- 17. Toward a more stable international monetary system: key takeaways / Atish R. Ghosh and Mahvash S. Quresh -- Index.
Includes bibliographical references and index
Keywords: Monetary Policy; MONETARY POLICY; INTERNATIONAL FINANCE; INTERNATIONAL COOPERATION; ECONOMIC POLICY; ECONOMIC RECESSION